Clinical Holistic Medicine: the “New Medicine”, the Multiparadigmatic Physician, and the Medical Record - Søren Ventegodt; Mohammed Morad; Joav Merrick (The Scientific World Journal)
The modern physician is often multiparadigmatic as he serves many different types of people in many different existential circumstances. The physician basically often has three, very different sets of technologies or “toolboxes” at his disposal, derived from three different medical paradigms: classical, manual medicine; biomedicine; and holistic or consciousness-oriented medicine. For lack of a better term, we have called the extended medical science — integrating these three different paradigms and their three strands of tools and methods — the “new medicine”. The excellent physician, mastering the “new medicine”, uses the most efficient way to help every patient, giving him or her exactly what is needed under the circumstances. The excellent physician will choose the right paradigm(s) for the person, the illness, or the situation, and will use the case record to keep track of all the subjective and objective factors and events involved in the process of healing through time. The case or medical record has the following purposes: A. Reflection: To keep track of facts, to provide an overview, to encourage causal analysis, to support research and learning, and to reveal mistakes easily. B. Communication: To communicate with the patient with a printout of the case record to create trust and help the patient to remember all assignments and exercises. C. Evidence and safety: To provide evidence and safety for the patient or to be used in case of legal questions. D. Self-discipline: To encourage discipline, as a good case record is basically honest, sober, brief, and sticks to the point. It forces the physician to make an effort to be more diligent and careful than a busy day usually allows.The intention of the case or medical record is ethical: to be sure that you, as a physician, give the best possible treatment to your patient. It helps you to reflect deeply, communicate efficiently, provide evidence and safety, and back your self-discipline, never to be carried away by the high speed of modern-day clinical work to give less than the optimal treatment. The patient's life, now and in the future, is in the palm of your hand, and to assume this huge responsibility, the physician must be anxious and careful about the quality of the medical record. Much too often, the essence of the session is nowhere to be found in the case record, so most of the generated value is lost between consultations.